Arginine and Vitamin E Improve the Cellular and Humoral Immune Response of Broiler Chickens - Abdukalykova, Saule; Ruiz-Feria, Ciro A. (International Journal of Poultry Science, 2006)
Two experiments were conducted to determine the effects of vitamin E (VE) and Arginine (ARG) on humoral and cellular immunity of broiler chickens, with 2 levels of ARG: normal (NARG, 1.2% in the feed) and high ARG (HARG, additional 0.3% ARG in the drinking water); and 3 levels of VE (40, 80, and 400 IU / kg feed). A corn-soybean meal diet and water were provided ad libitum throughout the study. Humoral immunity was measured as antibody responses to an i.p. injection of sheep red blood cells (SRBC, 10% solution) at d 25 followed by agglutination assay 4, 8, and 16 d after injection (Experiment 1). Cell-mediated immune response was assessed by the cutaneous basophil hypersensitivity test to phytohemagglutinin (PHA)-P at d 17 (Experiment 1) and PHA-M at d 41 (Experiment 1 and 2). Four d after SRBC injection the antibody titers (log2) were higher in HARG than in NARG birds (P < 0.01), and in VE-80 compared with VE-40 and VE-400 birds (P < 0.001). At 8 and 16 d the antibody titers were not different between ARG levels, but the VE-80 birds maintained higher antibody titers (P < 0.001) than VE-40 and VE-80 birds. Naive birds fed HARG showed a higher response than NARG birds (P < 0.05) to PHA-P at d 17 and to PHA-M at d 41, but after a second exposure ARG levels did not have a significant effect. Birds fed VE-400 had a lower response to PHA than birds fed VE-40 and VE-80 birds (P < 0.001) at d 41. These results show that high levels of ARG accelerate antibody production whereas VE at 80 IU kg / feed maintains a proper immune function over time, suggesting that ARG and VE may have complimentary effects on the immune function and health of broiler chickens.